Pengaruh Strategi Branding dan Ekuisitas Merek Terhadap Loyalitas Pasien di RS Permata Bunda Babat Lamongan - Muhamad Tsalis Fithrony; Masruroh Masruroh; Nasrudin Nasrudin (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to analyze the influence of branding strategy and brand equity on patient loyalty at Permata Bunda Hospital, Babat, Lamongan, both partially and simultaneously. The study, conducted at Permata Bunda Hospital, used a quantitative approach with an analytical cross-sectional study design with a research sample of 421 respondents who met the inclusion criteria with a systematic random sampling technique. There is a significant and strong influence between branding strategy and patient loyalty at Permata Bunda Hospital, Babat, Lamongan. The results of the Chi-Square test showed a Pearson Chi-Square value of 332.597 with a p-value = 0.000 (p <0.05), confirming a statistically significant relationship. The strength of the relationship is indicated by the Pearson's R correlation value of 0.741, indicating a strong positive correlation. Brand equity has been proven to be a very strong and reliable predictor of patient loyalty, with the strength of the relationship even higher than branding strategy.